INCIDENCIA DEL CRECIMIENTO ECONÓMICO EN EL USO DE ENERGÍAS RENOVABLES EN AMÉRICA DEL SUR EN EL PERIODO 1990-2015 - Japón Sánchez, Yandri Manuel (2019)
Theoretically it is said that as countries become richer, they tend to be more concerned about the environment; given the unprecedented economic growth experienced by the countries that make up South America, suggests that they would be more aware of what environmental care has been concerned, at least in terms of generation and sustainable energy consumption. That is why the research entitled , was carried out, which had as a general objective "Determine the influence of economic growth, measured by the Gross Domestic Product, in the use of renewable energies in the South America region, during the period 1990-2015 ". The investigative techniques used were the bibliographic, statistical and econometric, likewise, a self-regressive vector model (VAR) and error correction model (VEC) of panel data was proposed. The results show that the GDP affects negatively the consumption of renewable energy of the countries belonging to South America with an elasticity of -0,016%, the variable consumption of renewable energy and GDP are of nature I (1), the same ones that are integrated In the long and short term, that is, they move together over time, so improving the structure of energy production is very necessary for the countries of South America, which although has seen growth in the last decades, it is still far from